Harmonisasi Hukum sebagai Perlindungan Hukum oleh Negara bagi Para Pihak dalam Transaksi Elektronik Internasional - Abdul Halim Barkatullah (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The main problems of this research are, first, why state intervention in the form of legal protection to relevant parties in international transaction is needed? Second, is legal harmonization able to become a solution in providing legal protection for relevant parties in electronic transactions? This research was a normative legal research. The research findings show that, first, the parties involved in international transactions in free trade era are in a very weak position. Legal protection to the rights of the parties in international transactions cannot be fulfilled by only one legal aspect, but by a set of legal system so that the rights of the parties involved in electronic international transactions can be maintained. Second, the state’s roles in providing legal protection for the parties involved in electronic international transactions are by: (i) abolishing legal obstacles and issuing regulation for transactions; (ii) providing facilities in the form of regulation of legal protection for the parties involved in international transactions which are done by the parties themselves (self-regulation); and (iii) the parties should be cautious when being involved in international trade transaction.